Miłość jako zmienny w czasie proces - opinie i doświadczenia kobiet I mężczyzn dotyczące przebiegu związku intymnego = Love as a process changing over time - opinions and experiences of women and men concerning the development of intimate relationships - Czernecka, Julita (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is to increase the knowledge of the development of romantic relationships, taking into account the subjective perspective of the respondents. The author analysed the opinions and experiences of the participants of the study about the intimate relationship as a process in time and those concerning the identi?cation and signi?cance of each stage of "living together". What became important were the answers to the questions of how the respondents talk about the course of their romantic relationships; whether in their case the relationship has a speci?c pattern and how they characterize its trajectory.
Keywords: miłość; związek miłosny; związek intymny; socjologa pary; fazy miłości; etapy miłości; love; romantic relationship; intimate relationship; sociology of the couple; love phases; love stages